College students’ cognition and attitude toward medical knowledge education after a global public health event - Xiang, Wei; Cao, Hui; Wu, Juan; Chen, Peiru; Chen, Qiong; Tao, Fenghua; Jiang, Ting (Frontiers in Public Health, 2025)
IntroductionThe past global public health event has heightened governmental and societal awareness of the importance of health and medical knowledge education. This study aims to investigate and compare the attitude and cognition of non-medical students and medical students toward medical knowledge education.MethodsA self-administered, anonymous questionnaire was voluntarily completed by 304 university students recruited through the Wen-Juan-Xing online platform via WeChat QR codes or website links. The survey assessed participants’ cognition and attitudes regarding medical education.Results and discussionResults indicated that the vast majority of students recognized the importance of promoting medical knowledge education to disseminate practical medical skills and health knowledge. Medical students demonstrated significantly deeper understanding of general medical knowledge and greater proficiency in practical medical skills compared to non-medical students. Among non-medical students, 63.4% identified the lack of dedicated medical curricula and training as the primary barrier to their learning of medical knowledge, while only 53.4% expressed satisfaction with their institution’s current medical education offerings. These findings underscore the critical role of medical knowledge education in enhancing public health literacy by disseminating general medical knowledge and practical skills. Non-medical institutions should prioritize medical education reforms, including innovative medical curricular designs and teaching methodologies, to better align with both student and societal demands for healthcare competency.